Do teachers spot AI? Evaluating the detectability of AI-generated texts among student essays - Fleckenstein, Johanna; Meyer, Jennifer; Jansen, Thorben; Keller, Stefan; Köller, Olaf; Köller, Jens (Computers and Education: Artificial Intelligence, 2024)
The potential application of generative artificial intelligence (AI) in schools and universities poses great challenges, especially for the assessment…
Keywords: /unread